Legacy of the Blast - Victim Assistance in the Eyes of the Treaty on the Prohibition of Nuclear Weapons - Catarina Gonçalves Vaz Carvalho (2024)
This paper examines the overall disarmament and non-proliferation architecture (Chapter 1), the profound humanitarian impacts of nuclear weapons, and their relation to the Sustainable Development Goals (Chapter 2) to establish the Treaty on the Prohibition of Nuclear Weapons’ pertinence and the need for a robust framework of victim assistance. Chapter 3 delves into the positive obligations outlined in the Treaty, exploring the key arguments surrounding the disproportionate burden placed on affected states, contrasted with the limited responsibility of user states. This analysis highlights the importance of respecting affected states’ sovereignty in establishing a victim assistance mechanism while recognising that user states, with their higher gross domestic products and resources, are better equipped to address the financial challenges that victim assistance inherently brings. National assistance plans and laws are revisited under Chapter 4, revealing significant shortcomings: apologies remain insufficient; national plans mostly rely on one-time lump sum compensations that fail to address the long-term impacts of nuclear weapons; second and third-generation victims are often overlooked. The importance of relieving victims from the burden of establishing a causal link to receive assistance is also emphasised. Finally, Chapter 5 considers the progress made in the State Parties’ Meetings, focusing on the potential creation of a trust fund. This fund can learn from the criticism drawn throughout the paper and encompass the recommendations outlined here – by prioritising capacity buildingthe fund should aim at long-term support rather than just temporary alleviation of suffering. Overall, this thesis argues that while the TPNW represents a big step towards assisting victims of nuclear explosions, the compromises made by the drafters in its responsibility framework – particularly the minimal accountability of user states – limit its full potential. Looking ahead, much can still be done to bolster the support for nuclear-affected states – both those who have already joined the Treaty and those that could be encouraged to join through these enhancements (e.g. the Marshall Islands) – and individuals.